Timing of deformation and the mechanism of cleavage development in a Newfoundland melange - Williams, Paul (Atlantic Geology, 1983)
This paper is concerned with two aspects of folding and cleavage development in the "Carmanvllle Ophlolitic MSlange" of Newfoundland. First it is concerned with the problem of the timing of deformation relative to llthification and metamorphism, and second it is concerned with development of the cleavage. According to previous interpretation the cleavage and associated folds are a product of soft-sediment deformation. The cleavage however, Is a second generation axial-plane structure and microstructural observations, presented here, show it to be later than the peak of metamorphism. Further, F2 folds occur in quartz veins where they are associated with a strong crystallographic fabric. The second generation structures are thus a product of hard-rock deformation. The origin of the F] folds however, remains equivocal. Dyke-like structures previously attributed to migration of thixotroplc melange units are also post llthification and are a product of faulting and metamorphic differentiation. The S2 cleavage Is largely a product of rotation. In the coarser sediments whole clasts are rotated into the cleavage plane. Within shale clasts and in shale beds the cleavage has developed principally as a result of transposition by mlcrofolding. Folding fabrics have been modi-fled by grain growth.